Penggunaan Tepung daun Indigofera dalam Formula Pakan Benih Ikan Nila (Oreochromis niloticus) - Putri, Rizqiyatul Fardila (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
Indigofera zollingeriana is a plant species from the Fabaceae family that belongs to the legume group and has potential as an alternative source of plant protein in fish feed formulations. This plant is known to contain important nutrients, such as crude protein 28.98%, fiber 8.49%, fat 3.30%, and minerals calcium 0.52% and phosphorus 0.34%. This study was conducted to determine the effect of adding Indigofera leaf flour to feed on the performance of Nile tilapia (Oreochromis niloticus) fingerlings with an initial weight of 1.06±0.48 grams and length of 4.06±0.53 cm. Feeding was conducted twice daily for 56 days. The study used a non-factorial completely randomized design (CRD) with five levels of flour concentration (20–40%) and three replications. The results showed that the addition of Indigofera flour significantly (p0.05) affected survival, growth, feed efficiency, and feed conversion ratio. The 40% concentration yielded optimal results with TKH of 88.3%, PPM of 3.47 cm, LPH of 2.81%, FCR of 1.65, and EPP of 80.8%.